Strategi Manajemen Risiko Teknologi Informasi Berbasis Studi Literatur - Sri Fuji Muliati; Fidi Supriadi; Dani Indra Junaedi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The increasing reliance on information technology (IT) across various sectors has led to the growing importance of managing IT risks effectively. Information technology systems are prone to a variety of risks, including cybersecurity threats, system failures, and human errors. These risks can have severe consequences, such as financial loss, data breaches, and operational disruptions. To address these challenges, organizations must adopt comprehensive risk management strategies. This literature-based study explores various approaches and frameworks for managing IT risks, such as ISO 27001, NIST, and OCTAVE, by reviewing existing research and methodologies. The study aims to identify best practices, challenges, and trends in the field of IT risk management, offering insights into how organizations can improve their risk management strategies to enhance the resilience of their IT systems. Through this literature review, the paper highlights the importance of a systematic approach to IT risk management and provides recommendations for organizations seeking to mitigate risks and safeguard their technological.